Synthesis and characterization of novel thieno[3,2-b]thiophene based metal-free organic dyes with different heteroaromatic donor moieties as sensitizers for dye-sensitized solar cells - Sara S. M. Fernandes (2017)
Four novel heterocycle dyes 3a-d were synthesized in order to study the variations produced in theoptical, electronic and photovoltaic properties by substitution of different electron-rich heterocyclicgroups to the thieno[3,2-b]thiophene system. The final push-pull conjugated dyes 3a-d were synthesized by Suzuki-Miyaura coupling reaction followed by Knoevenagel condensation of the corresponding aldehyde precursors with cyanoacrylic acid 2a-d. These new push-pull systems are based ona thieno[3,2-b]thiophene spacer, a cyanoacetic acid anchoring group and several electron-richheterocycles (thiophene, pyrrole and furan) as donor groups. The multidisciplinary study concerningthe optical, redox and photovoltaic characterization of the dyes reveals that compound 3b bearing ahexyl-bithiophene donor group/heterocyclic spacer exhibits the best overall conversion efficiency(2.49%) as sensitizer in nanocrystalline TiO2 dye sensitized solar cells. Co-adsorption studies betweenN719 and 3b revealed that upon addition of N719 co-adsorbent, the optimized cell efficiencies wereimproved by 16e77%. The best efficiency was 4.40%, corresponding to 54% of the photovoltaic performance of the N719-based DSSC fabricated and measured under similar conditions